Gender Differences in Early Retirement Behaviour - Svenn-Åge Dahl; Øivind Anti Nilsen; Kjell Vaage (Institute for the Study of Labor (IZA), 2002)
In this paper we analyse early retirement for men and women focusing on family characteristics such as marital status, spouse income and wealth, and spouses? labour market status. The female participation rate is high in Norway, implying that the country is particularly suitable for the study of gender differences in the early retirement behaviour. At our disposal we have administrative data that include information on individuals aged between 55 and 61 years in 1989. The individuals are followed until the end of 1995, with the aim of determining the predictors of different early retirement states. The results of a competing risk model indicate that women are less likely to take early retirement compared to men and that these differences are due to both different characteristics and different behaviour.
Keywords: C23; J26; C25; 330; early retirement; gender differences; labour force participation; Flexible Altersgrenze; Geschlecht; Norwegen